How to Foresee the Future of Philosophy: Franz Brentano’s “Law of the Four Stages” - Norkus, Zenonas (Problemos, 1989)
The historico-philosophical conception of the Austrian philosopher Franz Brentano (1838-1917) is analysed. According to the philosopher, the ancient philosophy, the medieval one, and that of modern times present each by itself the three cycles in the evolution of philosophy, each of them including the scientific, the dogmatic, the sceptic and the mystic phases. However, the author of the article considers that in fact F. Brentano deals with the periodical mutual replacements of rationalistic and irrationalistic forms of idealism, conditioned by the development of material infrastructures.